MODEL POLA PRODUKSI GULA AREN PEDAWA BERBASIS KEARIFAN LOKAL - Putu Arvianto Kurnia Chandra; I Gusti Made Dharma Hartawan (JURNAL ILMIAH EDUNOMIKA, 2023)
Production activity is an activity to produce goods or services in order to increase the economic value of the goods or services themselves. Production is also an effort to create superior products. This study aims to analyze the palm sugar production model and the way palm sugar farmers maintain the quality of their production process to build an image in the eyes of palm sugar consumers and analyze local wisdom that is used as the basis for palm sugar production in pedawa village, Banjar sub-district, Buleleng Regency, Bali Province. This research is a qualitative research, data collection techniques by observing the palm sugar production process, interviewing farmers and village communities and reviewing supporting documents. Test the validity of the data using persistence of observation, detailed descriptions, Peer de Briefing with observers or researchers and triangulation. Data analysis uses data reduction, data presentation, and drawing conclusions. The results of the study stated that 1) The production model of Pedawa palm sugar starts from the process of making jaka to ngelebengang. 2) In maintaining the quality of the production process, palm sugar farmers are always consistent with the procedures that have been passed down from generation to generation and are standard in nature. 3) In producing palm sugar, basically Pedawa palm sugar farmers still maintain local traditions and are always guided by the spirit of local wisdom.